Norms assimilation in heterogeneous agent community - Mahmoud M.A.; Ahmad M.S.; Yusoff M.Z.M.; Mustapha A. (Springer Verlag, 2023)
This paper proposes a norms assimilation theory, in which a new agent attempts to assimilate with a social group’s norms. This theory builds an approach to norm assimilation, analyzes the cases for an agent to decide to assimilate with a social group and develops a mathematical model to measure the assimilation cost and the agent’s ability. Developing the norms assimilation theory is based on the agent’s internal belief about its ability and its external belief about the assimilation cost of a number of social groups. From its belief about its ability and assimilation cost, it is able to decide whether to proceed or decline the assimilation with a specific social group or join another group. © Springer International Publishing Switzerland 2014.